2020
DOI: 10.1097/yct.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroconvulsive Therapy on Short-Term Suicide Mortality in a Risk-Matched Patient Population

Abstract: Objective Although evidence has suggested that electroconvulsive therapy (ECT) is effective in reducing suicidal ideation, research establishing the effectiveness of ECT in reducing short-term risk of death by suicide is less conclusive. This study assessed whether receipt of ECT reduced suicide mortality among patients seeking healthcare in Veterans Health Administration hospitals. Methods Annual cohorts of patients who received ECT between 2006 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Electroconvulsive therapy (ECT) is safe and effective in reducing suicidal ideation in drug-resistant depression and schizophrenia in adults and adolescents, including population of pregnant women [118][119][120]. Interestingly, some data suggest that pre-ECT high level of TNF-α predicts a good response to ECT [121], and electroconvulsive therapy decreases inflammatory mediators [122].…”
Section: Therapeutic Options To Prevent Suicidementioning
confidence: 99%
“…Electroconvulsive therapy (ECT) is safe and effective in reducing suicidal ideation in drug-resistant depression and schizophrenia in adults and adolescents, including population of pregnant women [118][119][120]. Interestingly, some data suggest that pre-ECT high level of TNF-α predicts a good response to ECT [121], and electroconvulsive therapy decreases inflammatory mediators [122].…”
Section: Therapeutic Options To Prevent Suicidementioning
confidence: 99%
“…Nor is there any evidence that ECT prevents suicide, as is so often claimed. In a study published since our review, 14 810 patients receiving ECT were 1.3 times more likely to die by suicide than 58 369 non-ECT controls (Peltzman 2020).…”
Section: Criticism Of the Review's Methodsmentioning
confidence: 89%
“…None of the five meta-analyses identified any studies showing long-term benefits. The review's conclusion that there is no evidence ECT prevents suicide, as often claimed, was subsequently confirmed by a study of 14,810 ECT patients and 58,369 controls (Peltzman, Shiner, & Watts, 2020). The review concluded:…”
Section: Practitioner Pointsmentioning
confidence: 91%